2015
DOI: 10.1159/000437387
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical Thyroid Dysfunction and Depressive Symptoms among the Elderly: A Prospective Cohort Study

Abstract: Background: Subclinical hypothyroidism has been associated with depressive symptoms in cross-sectional studies, but prospective data and data on subclinical hyperthyroidism are scarce. Methods: In the Leiden substudy of the Prospective Study of Pravastatin in the Elderly at Risk (PROSPER), thyroid-stimulating hormone and free T4 levels were measured at baseline and repeated after 6 months in adults aged 70-82 years with preexisting cardiovascular disease or known cardiovascular risk factors to defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
28
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 45 publications
3
28
0
5
Order By: Relevance
“…B. 's et al and Delitala, A. P.'s et al studies confirmed thyroid hormone relates to depression, while some other articles concluded that no significant difference in depressive symptoms has been found between euthyroid and SCH patients [27][28][29][30][31] . Recently, Kim, M. D. et al found that depressed individuals with SCH are more likely to meet the criteria for MetS, indicating the existence of the complicated relation among depression, SCH and MetS 32 .…”
Section: Discussionmentioning
confidence: 90%
“…B. 's et al and Delitala, A. P.'s et al studies confirmed thyroid hormone relates to depression, while some other articles concluded that no significant difference in depressive symptoms has been found between euthyroid and SCH patients [27][28][29][30][31] . Recently, Kim, M. D. et al found that depressed individuals with SCH are more likely to meet the criteria for MetS, indicating the existence of the complicated relation among depression, SCH and MetS 32 .…”
Section: Discussionmentioning
confidence: 90%
“…For example, some studies applied drug utilization approaches or electronic health record analysis based on prescriptions data, pharmacy claims, or surveys to identify consumption of antithyroid medication and estimate the prevalence of treated hypothyroidism [21, 51-54]. Furthermore, many studies investigated the prevalence of this disorder or its role as a risk factor for other diseases in specific populations, for example in pregnant women, patients with diabetes, patients with cardiovascular diseases, or immunocompromised individuals [12, 24, 55-59]. Therefore, there is room and need for systematically review of the evidence on the prevalence of undiagnosed hypothyroidism in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Berent et al represented that free thyroid hormone concentrations were associated with depression severity (9). Blum et al's study revealed that after a three-year follow-up, depressive symptoms were not associated with hypothyroidism in the elderly population; however, GDS scores were significantly higher in hyperthyroid patients (8). Kamble et al reported a significant decrease in the T3 level and an increase in the T4 level in depressed middle-aged adults (mean age 40.2 ± 10.3 years) (20).…”
Section: Discussionmentioning
confidence: 98%
“…Thyroid hormones have well-known impacts on metabolic activities in the adult brain and thyroid dysfunction has been associated with different neuropsychiatric problems such as depressive disorders. The American Psychiatric Association guidelines suggest a thyroid function examination when evaluating depressive patients (8). Previous studies demonstrated various associations between depressive symptoms and thyroid function; some showed this association with hypothyroidism; some others with hyperthyroidism; and a few studies reported the association between depression and euthyroidism (8-12).…”
Section: Introductionmentioning
confidence: 99%